2022
DOI: 10.1049/rpg2.12442
|View full text |Cite
|
Sign up to set email alerts
|

A grid reinforcement approach for an optimized planning of high‐voltage distribution grids under consideration of line loading indicators

Abstract: This paper presents a new time‐series‐based approach for the planning of high‐voltage distribution grids, with the aim to use the existing grid structure in the best possible way and to enable an optimal integration of renewable energies sources (RES) into the existing grid structure. For planning the grid, the required grid reinforcements should be carried out in a clearly defined manner and should be targeted to be as low as possible. For this purpose, first the developed planning method determines the line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…At the same time, the grid topology information was considered to realize efficient expansion. The outcomes revealed that the ability of the method has high efficiency (Miller et al 2022). Paul et al proposed a new transformerless microinverter topology.…”
Section: Related Workmentioning
confidence: 99%
“…At the same time, the grid topology information was considered to realize efficient expansion. The outcomes revealed that the ability of the method has high efficiency (Miller et al 2022). Paul et al proposed a new transformerless microinverter topology.…”
Section: Related Workmentioning
confidence: 99%